The Utilization of the Canva Application as A Media for Arabic Learning at MTs Negeri Sungai Jambu - Amrina Amrina; Adam Mudinillah; Durrotul Hikmah; Muhammad Abdul Hamid (Acitya: Journal of Teaching and Education, 2022)
This article is development research that relies on several points of view that are obtained and described. Using qualitative descriptive. This discussion is about the use of the Canva application as a learning medium at MTsN Sungai Jambu, learning media is needed by teachers in supporting and supporting learning and education in their schools. Technological developments are increasingly rapid and advanced, everyone has the right to use technology to support activities in teaching, because with Using technology we can know easily or get information easily, and technology is also created to help human activities. Technology can not be separated from human life because of human technology can do all the work easier and faster. Technological progress is unavoidable from human life. The progress of technology will go hand in hand with the progress of science. The development of technology is very important for humans as a supporter of the progress of human life. Technological developments are developing drastically and continuously evolving. Each progress has its own impact on human life. So the development of this technology has an impact on changes in several aspects of life, there are negative and positive. Basically, the development of technology is actually to facilitate human work. Canva is an online-based application that provides attractive designs in the form of templates, features, and categories given in it, so teachers can take advantage of this Canva application for school progress.